Taxonomic identity of Cestrum benghalense (Solanaceae): A New Synonym of Cestrum aurantiacum - Sahoo, Phani Bhusan; Dash, Sudhansu Sekhar (Phytotaxa, 2025)
The taxonomic identity of Cestrum benghalense is evaluated and determined to be conspecific with Cestrum aurantiacum. To support this taxonomic revision, a detailed morphological description, photographic documentation, phenological information, and distributional data are presented.